Pengaruh strategi student teams achievement divisions (stad) dan team assisted individualization (tai) terhadap Hasil belajar matematika ditinjau dari kedisiplinan Siswa kelas vii di smp negeri 2 banyudono Tahun ajaran 2015/2016 - Nur Pamungkas, Luthfi, Drs Slamet HW, M.Pd (2016)
This study aims to describe and analyze: (1) the effect of learning strategy of Student Teams Achievement Divisions (STAD) and Team Assisted Individualization (TAI) in mathematics learning outcomes; (2) the effect of the dicipline of students direct learning in mathematics learning outcomes; (3) The interaction strategy of Student Teams Achievement Divisions (STAD) and Team Assisted Individualization (TAI) in termsof the discipline of students in mathematics learning outcomes. The reseach was conducted students of VII Grade of SMPN 2 Banyudono of even semester of Academic Year 2015/2016 with the population all students of VII a number of 267 students of class VII student. Type of the research is experiment with quasi experimental design. The class sample on reseach by using the strastified cluster random sampling. Methods of data collection use the test, questionnaire and documentation. Data analyzed using analysis of variance with two different cell lines. The results of data analysis with a significance level of 5% was obtained: (1) there is effect strategy of Student Teams Achievement Divisions (STAD) and Team Assisted Individualization (TAI) in mathematics learning outcames with FA=9.783 (2) there is effectsof the discipline of students (high, medium, low) in mathematics learning outcames with FB =12.711, (3) there is no interaction the learning strategy of student Teams Achievement Divisions (STAD) and Team Assisted Individualization (TAI) in terms of the discipline of students in mathematics learning outcames with FAB=1,588.